2015
DOI: 10.1007/s12020-015-0526-9
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid nodules ≤5 mm on ultrasonography: are they “leave me alone” lesions?

Abstract: The incidence of small thyroid malignancy has increased. However, there is no evidence-based guideline for managing thyroid nodules ≤ 5 mm on ultrasonography (US). We evaluated how to manage thyroid nodules ≤ 5 mm. Thyroid nodules ≤ 5 mm in size on US that had undergone surgery and US-guided fine-needle aspiration were eligible. A total of 3,117 thyroid nodules in 3,012 patients were included. The size changes of malignant and benign nodules during follow-up were evaluated. Thyroid malignancies were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
7
0
4
Order By: Relevance
“…Shimamoto et al 14 studied sonographic prediction in staging of papillary cancer and found that the sensitivity of sonography for detection of extracapsular extension of a tumor into the prethyroidal muscles and sternocleidomastoid was 77.8%, but the sensitivity values for invasion into the trachea and the esophagus were only 49% and 28.6%, respectively. That study, from 1998, used lower-frequency transducers (7.5-10 MHz) than our study (12)(13)(14)(15)(16)(17)(18) and was performed before the widespread use of harmonic imaging, compound imaging, and other sonographic techniques that have improved the resolution of sonography in current practice. A different study by Yamamura et al 15 from 2002 had much better results using preoperative sonography for detection of cancer invasion of the airways and found that sonography had an 83.3% accuracy rate, which was better than magnetic resonance imaging or computed tomography.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Shimamoto et al 14 studied sonographic prediction in staging of papillary cancer and found that the sensitivity of sonography for detection of extracapsular extension of a tumor into the prethyroidal muscles and sternocleidomastoid was 77.8%, but the sensitivity values for invasion into the trachea and the esophagus were only 49% and 28.6%, respectively. That study, from 1998, used lower-frequency transducers (7.5-10 MHz) than our study (12)(13)(14)(15)(16)(17)(18) and was performed before the widespread use of harmonic imaging, compound imaging, and other sonographic techniques that have improved the resolution of sonography in current practice. A different study by Yamamura et al 15 from 2002 had much better results using preoperative sonography for detection of cancer invasion of the airways and found that sonography had an 83.3% accuracy rate, which was better than magnetic resonance imaging or computed tomography.…”
Section: Discussionmentioning
confidence: 97%
“…Fourth, we excluded microcarcinomas in our study, for which treatment remains controversial. Some authors suggest that microcarcinomas may be safely observed, 13,17 and a recent article by Chéreau et al 18 suggested that microcarcinomas with extracapsular extension have outcomes that are similar to those of T2 disease. Although we think this topic requires further investigation, because of the retrospective nature of our study we excluded microcarcinomas to accurately correlate pathologic results with sonographic findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 5 mm as measured by examination certainly could be an appropriate threshold for treatment with surveillance. In addition, Moon et al [ 24 ] found that only 1.2% of thyroid malignant nodules measuring ≤5 mm on ultrasonography increased to >3 mm within 12 months, indicating that PTMC lesions of ≤5 mm were less likely to develop. Their study also supports our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies agree that there is no significant enlargement during follow-up in most of cases [7]. In small nodes (for instance smaller than 5 mm) the cytological report may bring some benefits in cases with changes of the diameters over time [8].…”
Section: Introductionmentioning
confidence: 93%